Neutralizing Enterovirus D68 Antibodies in Children after 2014 Outbreak, Kansas City, Missouri, USA - Livingston, Robyn A.; Harrison, Christopher J.; Selvarangan, Rangaraj (Emerging infectious diseases, 2022)
Enterovirus D68 (EV-D68) causes severe respiratory illness outbreaks among children, particularly those with asthma. We previously detected neutralizing antibodies against the predominant EV-D68 B1 clade in the 2014 outbreak in serum collected before the outbreak (2012–2013) from persons 24 months to 85 years of age. We recently detected neutralizing antibodies to the 2014 B1, B2, and D clade viruses in serum collected after the 2014 outbreak (April–May 2017) from 300 children 6 months to 18 years of age. B1 virus neutralizing antibodies were found in 100% of patients, even children born after 2014; B2 in 84.6%, and D in 99.6%. In 2017, titers increased with patient age and were higher than titers in 2012–2013 from comparably aged children. Rate of seronegativity was highest (15.3%) for B2 virus. Multivariate analysis revealed an association between asthma and higher titers against B2 and D viruses. EV-D68 seems to have circulated during 2014–2017.